A bargaining perspective on vertical integration - Hendrik Döpper; Geza Sapi; Christian Wey (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2022)
This paper analyzes vertical integration incentives in a bilaterally duopolistic industry where input market outcomes are determined by bargaining. Vertical integration incentives are a combination of horizontal integration incentives up- and downstream and depend on the strength of substitutability or complementarity and the shape of the unit cost function. In contrast to the widely prevailing view in competition policy, vertical integration can under particular circumstances convey more bargaining power to the merged entity than a horizontal merger to monopoly. In a bidding game for an exogenously determined target firm, a vertical merger can dominate a horizontal one, while pre-emption does not occur.
Keywords: L13; L22; L42; 330; Bargaining; Vertical Mergers; Shapley Value